2017
DOI: 10.1155/2017/4180703
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Cell Line Secretome Highlights the Roles of Transforming Growth Factor-Beta-Induced Protein ig-h3, Peroxiredoxin-2, and NRF2 on Cervical Carcinogenesis

Abstract: Cancer cells acquire unique secretome compositions that contribute to tumor development and metastasis. The aim of our study was to elucidate the biological processes involved in cervical cancer, by performing a proteomic analysis of the secretome from the following informative cervical cell lines: SiHa (HPV16+), HeLa (HPV18+), C33A (HPV−), and HCK1T (normal). Proteins were analyzed by 2D gel electrophoresis coupled to MALDI-TOF-MS. Enrichment of secreted proteins with characteristic profiles for each cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 45 publications
(55 reference statements)
0
41
1
Order By: Relevance
“…Most of the proteomic studies utilizing cervical cancer cell lines, focus on the differences that occur in the protein expression pattern as an effect of a drug treatment, such as doxorubicin, oxymatrine and cisplatin (43)(44)(45), or under stress conditions, like UVB irradiation and hypoxia (46,47), or after the induced and/or inhibited expression of specific genes, as in the cases of HVP16 E6 gene, transgelin-2 and parkin (48)(49)(50). Moreover, our group has recently studied the secretome of these cervical cancer cell lines compared to normal cervical keratinocytes (8). Comparative analysis of the secretome revealed 67 differentially expressed proteins, out of which 36 were also identified as differentially expressed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the proteomic studies utilizing cervical cancer cell lines, focus on the differences that occur in the protein expression pattern as an effect of a drug treatment, such as doxorubicin, oxymatrine and cisplatin (43)(44)(45), or under stress conditions, like UVB irradiation and hypoxia (46,47), or after the induced and/or inhibited expression of specific genes, as in the cases of HVP16 E6 gene, transgelin-2 and parkin (48)(49)(50). Moreover, our group has recently studied the secretome of these cervical cancer cell lines compared to normal cervical keratinocytes (8). Comparative analysis of the secretome revealed 67 differentially expressed proteins, out of which 36 were also identified as differentially expressed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, utilization of informative cell lines with or without the HPV genome, can provide valuable insights on these mechanisms. To this end, our group has initiated a comprehensive approach to elucidate the specific oncogenic drivers operating in cervical cancer, both at the transcriptional (7) and the proteomic level (8). In these studies, we have identified for the first time, four novel transcription modules (7), involved in cervical cancer, exhibiting synergy between groups of transcription regulators, while certain modules were annotated to specific biological processes, such as cell cycle, apoptosis, transcription and development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ΗCK1T cells were a kind gift of Dr. Tohru Kiyono (13), and were cultured as proposed (13), in Defined Keratinocyte Serum-Free Medium (Gibco BRL, San Francisco, CA, USA), supplemented with 5 ng/ml Epidermal Growth Factor (Gibco BRL) and 50 μg/ml of Bovine Pituitary Extract (Gibco BRL). The collection of secretome as well as the total cell extract was performed as previously described by our group (12,15).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the secretome can be a source of putative biomarkers that can be easily detected in biological fluids, such as serum of cancer patients (10,11). We have recently compared the secretome of three representative cervical cancer cell lines (12), such as the C33A (HPV negative), SiHa (HPV16 + ), and HeLa (HPV18 + ) cell lines, to a normal cervical keratinocyte cell line, HCK1T (13), by employing two-dimensional gel electrophoresis coupled to MALDI-TOF mass spectrometry. This initial analysis revealed aberration of several canonical pathways involving metabolic processes and the activation of NRF2-mediated oxidative stress response in cervical cancer cells (12).…”
mentioning
confidence: 99%